Founder management and the market for corporate control for IPO firms: The moderating effect of the power structure of the firm - Gao, Ning; Jain, Bharat A. (Journal of Business Venturing, 2012)
This study draws on agency and stewardship theory to evaluate the relationship between alternative governance regimes (founder versus non-founder CEO) adopted at the time of going public on post-IPO economic outcomes in the market for corporate control. We find that the presence of founder CEOs reduces the likelihood of post-IPO change of control but enhances target IPO firm wealth by increasing acquisition premiums. Additionally, we examine whether measures of CEO power over the board moderate the relationship between founder management and target IPO firm wealth. Our results suggest that CEO duality is the most effective instrument of CEO power available to founder CEOs to positively influence target firm wealth. Further, we find that while founder CEOs utilize power derived from CEO duality to increase acquisition premiums, non-founder CEOs use board leadership power to expropriate shareholder wealth.